2019
DOI: 10.1002/cam4.2394
|View full text |Cite
|
Sign up to set email alerts
|

PD‐L1 and PD1 expression in post‐transplantation lymphoproliferative disease (PTLD) of childhood and adolescence: An inter‐ and intra‐individual descriptive study covering the whole spectrum of PTLD categories

Abstract: Therapy of children with post‐transplantation lymphoproliferative disorder (PTLD) after hematopoietic stem cell (HSCT) and solid organ transplantation (SOT) can be challenging. In this retrospective study, we investigated PD‐L1 and PD1 expression in all PTLD categories of childhood and adolescence to see whether checkpoint inhibition with PD‐L1/PD1 inhibitors may serve as a therapy option. We included 21 patients aged 19 years or younger (at date of transplant) with PTLD following SOT or HSCT having adequate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 39 publications
2
16
0
Order By: Relevance
“…29,31 The frequency of PD-L1 positive pediatric PTLD-DLBCL cases (72.7%) was similar to other pediatric and adult PTLD-DLBCL cohorts that reported approximately 60-80% positivity. 13,34,41 Despite defining 5% as the threshold for PD-L1-positivity, all PD-L1-positive cases in our cohort showed at least 30% positive membranous staining. Kiyasu et al 29 employed a similar cut-off in adult DLBCL and reported PD-L1 positivity ranges from 30% to 100% while observing a marked decrease in staining below the 30% threshold.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…29,31 The frequency of PD-L1 positive pediatric PTLD-DLBCL cases (72.7%) was similar to other pediatric and adult PTLD-DLBCL cohorts that reported approximately 60-80% positivity. 13,34,41 Despite defining 5% as the threshold for PD-L1-positivity, all PD-L1-positive cases in our cohort showed at least 30% positive membranous staining. Kiyasu et al 29 employed a similar cut-off in adult DLBCL and reported PD-L1 positivity ranges from 30% to 100% while observing a marked decrease in staining below the 30% threshold.…”
Section: Discussionmentioning
confidence: 76%
“…PD-1 IHC staining (clone MRQ-22, Cell Marque) was performed at a 1:50 dilution on an automated Leica Bond III immunostainer. All PD-1/PD-L1 IHC results were independently reviewed and scored by two hematopathologists as previously described 34 with a few modifications (Supplemental Table 1). Membranous PD-L1 staining of tumor cells and macrophages, and membranous PD-1 staining of tumor infiltrating lymphocytes (TIL) were scored for staining intensity: 0 (no staining), 1+ (weak or equivocal), 2+ (moderate), 3+ (strong).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Maintenance of graft tolerance is related to the interaction between PDCD1 (PD-1) and PD-L ( 43 ). Post-transplantation lymphoproliferative disorder, which was developed under the condition of T-cell dysfunction or immunosuppression after HSCT, is also related to the expression of PDCD1 ( 44 ). Among the SNPs, rs5839828 and rs36084323 are within the promoter region, rs6705653 and rs41386349 are in intron 4, and rs2227982 is in exon 5.…”
Section: Discussionmentioning
confidence: 99%
“…The potential use of checkpoint inhibition in patients with PTLD has been fueled by the high expression of PD-1 (programmed cell death 1 protein) and PD-L1 (programmed cell death 1 ligand 1) in PTLDs, in particular in EBV-positive cases, which are mainly driven by 9p24.1 gain/amplification. [67][68][69][70] However, switching on the immune system may cause a substantial risk for graft rejection, and this may also complicate the use of chimeric antigen receptor T-cell (CAR-T) therapy, given the potentially impressive cytokine storm associated with this therapy. Krishnamoorthy et al recently reported on the use of CAR-T in solid organ transplantation-related PTLD (including 2 KTRs).…”
Section: Checkpoint Inhibition and Chimeric Antigen Receptor T Cellsmentioning
confidence: 99%